Pengelolaan Keuangan Pribadi : Pengendalian Diri Terhadap Penggunaan Uang Bagi Karyawan - Chandra Hariwijaya; Maria Rio Rita (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2018)
The aim of this study is to find out what kind of self-control on the use of money, especially for employees. The population in this study were academic and non-academic employees at Satya Wacana Christian University, Salatiga. The sample was chosen by using convenience sampling method. To capture the phenomenon of self control on money using, the research instrument is prepared in the form of a questionnaire containing the form, manner and reason of self-control in the use of money. The analysis will be presented in descriptive form by utilizing the frequency distribution.The results shown that the most kind of self-control on the use of money that used by employees of Satya Wacana Christian University, using many efforts to control their finance, like set aside money each month for savings, prioritize the critical needs, reduce spending and record the expenses.